Legal bases for counteracting financial terrorism - I. V. Kyrieieva; А. І. Denysov (Law and Safety)
The legal regulation of the basics for counteracting financial terrorism in connection with financial security has been studied. It has been established that financial terrorism can be considered as a multifaceted phenomenon, and therefore it is extremely dangerous for national economic interests. Financial terrorism is primarily a threat to the economic interests of the state, and therefore threatens national security in general. The fight against financial terrorism is directly linked to financial security. It has been established that financial security is an integral element of economic security, which, in turn, is a part of the national security of the state. The views of scientists on the content and essence of financial security have been studied, on the basis of which a conclusion has been made about the characteristics of financial security as a state of prevention of financial terrorism. It has been concluded that financial security has the following features: future orientation, dynamism, focus on sustainable growth, priority of national economic interests, economic independence of the state, its independence from the influence of external capital, which is especially relevant in external aggression. The content of the main normative legal acts, which determine the basic principles of counteraction to financial terrorism in the context of the principles of legal regulation of tax, foreign economic and other economic activity as a means of financial security, has been analyzed. It has been concluded that the fight against financial terrorism is a system of legal, organizational, financial, economic and methodological measures aimed at ensuring the protection of the financial interests of the state as the financial basis of its activities, prevention of real and projected threats. The classification of legal bases for counteracting financial terrorism on specificity of a direction has been offered; the general economic bases and financial and legal bases which are those guiding principles which are revealed in regulation of financial and legal relations, and also financial and security bases have been allocated. It has been noted that the implementation of reforms on Ukraine's European integration becomes possible only under the conditions of legal consolidation, detailing and observance of the legal bases of counteraction to financial terrorism in those normative and legal acts, which regulate the issues of financial security.